2004
DOI: 10.1007/s00249-004-0422-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the interaction of the bacterial protease OmpT with outer membrane lipids and biological activity of OmpT:lipopolysaccharide complexes

Abstract: Outer-membrane proteases T (OmpT) are important defence molecules of Gram-negative bacteria such as Escherichia coli found in particular in clinical isolates. We studied the interaction of OmpT with the membrane-forming lipids phosphatidylethanolamine (PE) and phosphatidylglycerol (PG) from the inner leaflet and lipopolysaccharide (LPS) from the outer leaflet of the outer membrane. These investigations comprise functional aspects of the protein-lipid interaction mimicking the outer-membrane system as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…It is difficult to understand the modulation pattern of OmpT and lipoprotein 28 (NlpA) observed in this work (Table 1). Brandenburg et al . (2005) and McCarter et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to understand the modulation pattern of OmpT and lipoprotein 28 (NlpA) observed in this work (Table 1). Brandenburg et al . (2005) and McCarter et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to understand the modulation pattern of OmpT and lipoprotein 28 (NlpA) observed in this work (Table 1). Brandenburg et al (2005) and McCarter et al (2004) have shown OmpT to be a major defence molecule in such Gram-negative bacteria as E. coli, whose function is to cleave antimicrobial peptides. Bodero et al (2007) and Yamaguchi & Inouye (1988) found that lipoprotein 28 is nonessential for cell growth under laboratory conditions, but they did not rule out the possibility that lipoprotein 28 plays an important role under certain condition.…”
Section: Discussionmentioning
confidence: 99%
“…The motif is made up by basic amino acids and shared by a number of prokaryotic and eukaryotic proteins which bind to lipopolysaccharide (LPS) (16); these include the Escherichia coli porin FhuA (17) and the human MD-2 protein that presents LPS to Toll-like receptor 4 (TLR4) (70). Indeed, the presence of LPS is needed to reactivate enzymatic function of the purified omptins OmpT of E. coli (6,37,38) and Pla of Y. pestis (39) reconstituted in detergent micelles, strongly suggesting that interaction with LPS is important for omptin functions in general. Further, the modification of LPS structure inside the mouse macrophage was recently found important for the high degree of in vivo activity of the PgtE omptin of Salmonella enterica (42).…”
mentioning
confidence: 99%
“…Omptins are unique proteases in that they require rough (short O side chain) LPS to be active (Kramer et al, 2000, 2002; Kukkonen et al, 2001, 2004; Brandenburg et al, 2005; Suomalainen et al, 2010). A consensus protein motif for binding to 4′-phosphate in lipid A (Ferguson et al, 2000) is present in the omptin barrel (Vandeputte-Rutten et al, 2001) and consists of R138 and R171 in Pla.…”
Section: Structure-function Relationships Of Plamentioning
confidence: 99%
“…Pla could potentiate growth of Y. pestis in the lungs through cleavage of pulmonary antimicrobial peptides (Galvan et al, 2008). In this context, it is interesting that OmpT has been suggested to induce cytokine responses independently of the omptin-bound LPS (Brandenburg et al, 2005). …”
Section: Pla Enhances Fibrinolysismentioning
confidence: 99%